Cultural-Historical Perspectives on Collective Intelligence Patterns in Problem Solving and Innovation - Baltzersen, Rolf K. (Social Sciences, 2022)
Social creatures, like humans, solve problems together. Collective intelligence is essential in all organizations and societies if we want to resolve humanity's greatest challenges. This book explores how to deploy new practices such as crowdsourcing and online knowledge sharing. This title is also available as Open Access on Cambridge Core.